1996
DOI: 10.1111/j.1600-0447.1996.tb09855.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders and comorbidity in attempted suicide

Abstract: The present study examined the prevalence and comorbidity of mental disorders according to DSM-III-R among male and female suicide attempters. A systematic sample of 114 patients from consecutive cases of attempted suicide referred to a general hospital in Helsinki between 1 January and 31 July 1990 was interviewed. In 98% of the cases at least one Axis I diagnosis was made. Depressive syndromes were more common among females (85%) than males (64%), and alcohol dependence was more common among males (64%) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
114
3
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(144 citation statements)
references
References 36 publications
22
114
3
5
Order By: Relevance
“…Other studies that did not use administrative data found that more than 80% of individuals had a psychiatric disorder at the time of a self-inflicted injury 4,5,7 ; in the present study, only 35% of self-inflicted injury visits had a mental disorder diagnosis coded (data not shown). However, despite the acknowledgment of underreporting of certain diagnoses, there is no reason to suspect that it would introduce a bias by being more or less prevalent in one of the study groups.…”
Section: Limitationscontrasting
confidence: 62%
“…Other studies that did not use administrative data found that more than 80% of individuals had a psychiatric disorder at the time of a self-inflicted injury 4,5,7 ; in the present study, only 35% of self-inflicted injury visits had a mental disorder diagnosis coded (data not shown). However, despite the acknowledgment of underreporting of certain diagnoses, there is no reason to suspect that it would introduce a bias by being more or less prevalent in one of the study groups.…”
Section: Limitationscontrasting
confidence: 62%
“…More specifically, pain-related physical conditions like migraine and back pain have been associated with an increased risk of suicidal behaviours (Ilgen et al, 2013;Smith et al, 2004) The influence of multiple mental illnesses on risk of suicide is of considerable interest from a global public health perspective. Several studies have reported that major depression, anxiety disorder and substance abuse are often found to co-occur with other psychiatric conditions within suicidal populations (Hawton et al, 2003a;Nock et al, 2010;Suominen et al, 1996). Such findings suggest an increased risk among people with specific multimorbid psychiatric diagnoses and highlight the need for more targeted support from mental health services (Andrews and Lewinsohn, 1992;Bronisch and Wittchen, 1994;Mościcki, 2001;Oquendo et al, 2005;Pawlak et al, 1999;Wunderlich et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…There appear to be parallels between patients who self harm and patients who have BPD. Studies have shown a high percentage of patients who self harm have a diagnosis of PD; 40% (Suominen et al 1996) and 46% (Haw et al 2001). However, some of these studies also looked at patient's intent to die using the Suicidal Intent Scale (SIS) (Beck et al 1974).…”
Section: Criterion -Borderline Personality Disordermentioning
confidence: 99%